P-Tolylimido rhenium(v) complexes with phenolate-based ligands: synthesis, X-ray studies and catalytic activity in oxidation with tert-butylhydroperoxide. Issue 1 (30th November 2015) - Gryca, Izabela; Machura, Barbara; Małecki, Jan Grzegorz; Kusz, Joachim; Shul'pina, Lidia S.; Ikonnikov, Nikolay S.; Shul'pin, Georgiy B.
Abstract : The reactions of mer -[Re( p -NTol)X3 (PPh3 )2 ] with phenolate-based ligands gave 16 new rhenium(v ) complexes. Only a few of them exhibited high catalytic activity. Abstract : The reactions of mer -[Re( p -NTol)X3 (PPh3 )2 ] (X = Cl, Br) with chelating phenolate-based ligands (2-(2-hydroxy-5-methylphenyl)benzotriazole (HL 1 ), 2-(2-hydroxyphenyl)benzothiazole (HL 2 ) or 2-(2-hydroxyphenyl)benzoxazole (HL 3 )) afforded a series of p -tolylimido rhenium(v ) complexes cis - or trans -(X, X)-[Re( p -NTol)X2 (L)(PPh3 )]· y MeCN (where X = Cl, Br; L = L 1, L 2, L 3 and y = 0–2) and [Re( p -NTol)X(L)(PPh3 )2 ]Z· p PPh3 (where X = Cl, Br; Z = ReO4, PF6 ; L = L 1, L 2, L 3 and p = 0 or 1). The reported compounds were characterized by elemental analysis, FT-IR, NMR ( 1 H, 13 C and 31 P) and X-ray crystallography. Interestingly, the halide ions of [Re( p -NTol)Cl2 (L 1 )(PPh3 )]·MeCN (1 ) and [Re( p -NTol)Cl2 (L 2 )(PPh3 )]·2MeCN (3 ) are in cis relative dispositions, whereas the complexes [Re( p -NTol)Br2 (L)(PPh3 )] (L 1 for2, L 2 for4 and L 3 for6 ) and [Re( p -NTol)Cl2 (L 3 )(PPh3 )] (5 ) were found to be trans -(X, X) isomers. The compounds [Re( p -NTol)X(L)(PPh3 )2 ](PF6 ) (X = Cl, Br; L = L 1 and L 2 ) and [Re( p -NTol)X(L 3 )(PPh3 )2 ](PF6 )·PPh3 (X = Cl, Br) have been tested in oxidative catalysis. A few compounds exhibited very good catalytic properties in oxidation of alcohols with tert -BuOOH (TBHP) in acetonitrile solution at moderate temperatures. Complex [Re( p -NTol)Cl(L 2 )(PPh3 )2 ]PF6 (13 ) is the catalyst of choice for oxidation of 1-phenylethanol to acetophenone (in 80% yield; turnover number attained 290 after 30 h) and cyclooctanol to cyclooctanone (in 88% yield). Notably lower activity has been found in the oxidation of alkanes with TBHP. Product distribution in the oxidation of methylcyclohexane indicates some steric hindrance around the reaction center.